From legal to normative: A combined social representations and sociocognitive approach to diagnosing cultural change triggered by new environmental laws. (September 2019) - Bertoldo, Raquel; Castro, Paula
Inconsistency between the expressed support for resource-conservation ideas and behaviours has emphasized the need to develop a better understanding of the psychosocial processes through which formal laws (reified universe) also become informal norms (consensual universe). Experimental paradigms of the sociocognitive approach to social norms are able to assess if cultural change fostered by the legal/reified universe has been incorporated by society to the level of influencing, and being expected, in interpersonal communications. This article proposes to combine elements from the social representations theory and the sociocognitive approach to social norms in a diagnose proposal for cultural change (appropriation and consensualization dimensions). Through a self-presentation paradigm, results of Study 1 show that conservation beliefs and behaviours are indeed used in interpersonal contexts in order to be well-seen; yet, this informal valorization is context-dependent. In Study 2, a hetero-evaluation paradigm was used. Results show that conservation beliefs are socially valued and crucial for people to be positively seen (appropriation). However, the expression of conservation behaviours is not required (consensualization). Overall, these results show that conservation beliefs and behaviours have become informal norms in Portugal. Still, this valorization is not yet homogeneous; it partially tolerates belief–behaviour inconsistency, a typical dynamic of emancipated representations.